2017
DOI: 10.1007/s12149-017-1228-6
|View full text |Cite
|
Sign up to set email alerts
|

A 3-variable prognostic score (3-PS) for overall survival prediction in metastatic castration-resistant prostate cancer treated with 223Radium-dichloride

Abstract: We propose a multidimensional clinical evaluation to select those mCRPC subjects suitable to receive the maximum benefit from Ra treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 23 publications
2
29
0
Order By: Relevance
“…This is in line with literature 16,17 and the results from the ALSYMPCA trial in which anaemia as a serious adverse event was reported in 8% of pts with radium-223 and in 9% of pts treated with placebo 10 . It is also in agreement with real-world experience 18 , and in a study in 92 pts with mCRPC only baseline haemoglobin and ECOG PS were www.nature.com/scientificreports www.nature.com/scientificreports/ significantly correlated with OS among all clinical parameters 19 . For this reason, in our opinion, early identification of pts with sideropenic anaemia in which an oral iron supplement was sufficient to restore haemoglobin levels and improve anaemia is mandatory 20,21 .…”
Section: Discussionsupporting
confidence: 89%
“…This is in line with literature 16,17 and the results from the ALSYMPCA trial in which anaemia as a serious adverse event was reported in 8% of pts with radium-223 and in 9% of pts treated with placebo 10 . It is also in agreement with real-world experience 18 , and in a study in 92 pts with mCRPC only baseline haemoglobin and ECOG PS were www.nature.com/scientificreports www.nature.com/scientificreports/ significantly correlated with OS among all clinical parameters 19 . For this reason, in our opinion, early identification of pts with sideropenic anaemia in which an oral iron supplement was sufficient to restore haemoglobin levels and improve anaemia is mandatory 20,21 .…”
Section: Discussionsupporting
confidence: 89%
“…Since its FDA approval and clinical introduction, lots of studies have been carried out concerning the clinical outcomes of 223-Radium dichloride (223-Ra) treatment in patients with metastatic castration-resistant prostate cancer (mCRPC) [6][7][8][9][10][11][12] . Despite this, to our knowledge, at present, it has never been reported the significance and pre-therapeutic prognostic value of previous primary radical treatment in patients treated with 223-Ra therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Besides documenting its effect on pain palliation, the pivotal phase 3 Alpharadin in Symptomatic Prostate Cancer Patients (ALSYMPCA) trial demonstrated the prognostic benefit that is induced by this radio-metabolic approach that prolonged overall survival (OS) and delayed time to the first symptomatic skeletal event with respect to the placebo arm [1]. However, in the last few years, some retrospective studies suggested that the OS benefit in real-life patients might be lower than that reported in the ALSYMPCA study [2][3][4][5]. These evidences might be explained either by the suboptimal sequence of Ra223 use in the castrate-resistant phase or as the result of a suboptimal selection of patients with poorer prognostic clinical characteristics.…”
Section: Introductionmentioning
confidence: 99%